2008
DOI: 10.1007/s11065-008-9054-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Contributions to the Early Identification of Alzheimer’s Disease

Abstract: A wealth of evidence demonstrates that a prodromal period of Alzheimer's disease (AD) exists for some years prior to the appearance of significant cognitive and functional declines required for the clinical diagnosis. This prodromal period of decline is characterized by a number of different neuropsychological and brain changes, and reliable identification of individuals prior to the development of significant clinical symptoms remains a top priority of research. In this review we provide an overview of those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
134
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(151 citation statements)
references
References 180 publications
(210 reference statements)
13
134
1
3
Order By: Relevance
“…Studies show that the risk of dementia of the Alzheimer's type increases dramatically in individuals between the ages of 65 and 85 (Bondi et al 2008), notably a similar range in which we report age-related sequence memory impairments. There is evidence to suggest that the prevalence of the disease may continue to increase into the ninth decade of life (Jorm and Jolley 1998;von Strauss et al 1999).…”
Section: Discussionsupporting
confidence: 80%
“…Studies show that the risk of dementia of the Alzheimer's type increases dramatically in individuals between the ages of 65 and 85 (Bondi et al 2008), notably a similar range in which we report age-related sequence memory impairments. There is evidence to suggest that the prevalence of the disease may continue to increase into the ninth decade of life (Jorm and Jolley 1998;von Strauss et al 1999).…”
Section: Discussionsupporting
confidence: 80%
“…However, it has been shown that impairment in the level of episodic memory may especially characterize prodromal states of Alzheimer's disease (AD), 40 and it may be effective in identifying those with a family history of AD. 44 Moreover, a neurocognitive profile characterized by pronounced deficits in executive functioning along with poor episodic memory (eg, recognition memory impairment) is typical in patients with early-onset AD. Furthermore, visual reproduction may be sensitive in detecting early AD.…”
Section: Resultsmentioning
confidence: 99%
“…42 Higher educational attainment has been shown to be related to later onset of AD 44 and to modify the association between AD-related neuropathology and neurocognitive functioning. 47 The finding that late preterm birth was not associated with performance on the CERAD-NB among those who had attained tertiary levels of education may indicate that their higher neurocognitive reserve mitigates the aging-related neurocognitive impairment.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have already highlighted that specific neuropsychological domains, such as episodic memory, executive function, language and attention, are particularly vulnerable to AD (Bondi et al, 2008), and that some of these domains can be positively affected by cognitive intervention (Cavallo et al, 2013a;Huntley et al, 2015), even if to date evidence in this direction is still growing. To the best of our knowledge, our study is one of the first showing at a large scale a clear and stable pattern of improved neuropsychological performances in AD patients due to the cognitive training implemented.…”
Section: Discussionmentioning
confidence: 99%